2020
DOI: 10.1038/s41388-020-1358-5
|View full text |Cite
|
Sign up to set email alerts
|

Wnt/β-catenin activation cooperates with loss of p53 to cause adrenocortical carcinoma in mice

Abstract: Adrenocortical carcinoma (ACC) is a rare and aggressive malignancy with limited therapeutic options. The lack of mouse models that recapitulate the genetics of ACC has hampered progress in the field. We analyzed The Cancer Genome Atlas (TCGA) dataset for ACC and found that patients harboring alterations in both p53/Rb and Wnt/β-catenin signaling pathways show a worse prognosis compared with patients that harbored alterations in only one. To model this, we utilized the Cyp11b2(AS) Cre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 47 publications
3
30
0
2
Order By: Relevance
“…Based on the aforementioned studies, the general pattern that emerges is that female mice are more prone to diseases of adrenocortical hyperactivity and tumorigenesis, while male mice are more prone to adrenocortical atrophy. However, not all adrenocortical tumor models display female bias: in a model of metastatic ACC induced by the combination of Trp53 deletion and β-catenin constitutive activation, no difference in the timing of tumor onset was observed between the sexes [ 48 ]. In another ACC model, due to Igf2 /H19 loss of imprinting and Apc deletion, hyperplasia is observed first in males [ 49 ].…”
Section: Sexual Dimorphism In the Adrenal Cortexmentioning
confidence: 99%
“…Based on the aforementioned studies, the general pattern that emerges is that female mice are more prone to diseases of adrenocortical hyperactivity and tumorigenesis, while male mice are more prone to adrenocortical atrophy. However, not all adrenocortical tumor models display female bias: in a model of metastatic ACC induced by the combination of Trp53 deletion and β-catenin constitutive activation, no difference in the timing of tumor onset was observed between the sexes [ 48 ]. In another ACC model, due to Igf2 /H19 loss of imprinting and Apc deletion, hyperplasia is observed first in males [ 49 ].…”
Section: Sexual Dimorphism In the Adrenal Cortexmentioning
confidence: 99%
“…In the genetic analysis of ACC, "ampli cation" (2.2%, n=91) was the main mutation type, and the effect of this mutation on ACC and downstream proteins remains to be further studied. Studies have shown that activate Wnt/β-catenin and delete p53 synergically induce adrenal cortical carcinoma in mice [24], and studies have shown that NRF1 has inhibitory effect on Wnt/β-catenin signal transduction in mouse liver [25]. However, the role of NRF1 in regulating of Wnt/β-catenin activation and p53 in adrenal cortical carcinoma remains to be further studied.…”
Section: Discussionmentioning
confidence: 99%
“…This model has allowed to prove the efficacy of mTORC1 inhibition by rapamycin on tumor development. Recently, Borges et al developed another ACC mouse model with simultaneous β-catenin activation combined with Trp53 deletion and observed ACC development with metastases [9]. NCI-H295R xenografts have been established and solid tumors were locally measurable, however no development of metastasis was observed in those tumor-bearing mice.…”
Section: In Vivo Modelsmentioning
confidence: 99%